2022
DOI: 10.1177/11786302221104949
|View full text |Cite
|
Sign up to set email alerts
|

Small Scale Enterprise Workers Require Attention: What Predicts the Level of Occupational Injuries?

Abstract: Background: Occupational injuries are among the foremost public health problems that small scale enterprise workers are encountering. Most foregoing occupational injury studies focused on construction or welding industry workers which could underestimate the real level of occupational injuries recorded in small scale enterprises. Conversely, others deal with a combined level of injuries from both small scale and large scale enterprises. Therefore, this study examined the magnitude and predictors of occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The study revealed that serious accidents frequently occurred at sites of less than 0.008 billion USD in South Korea. Collectively, these studies, including contributions by Daba et al [10] and Berhe et al [11], consistently show that workers in smaller construction sites are at a higher risk compared to those in larger settings.…”
Section: Accident Characteristics In Small-scale Construction Sitesmentioning
confidence: 77%
See 1 more Smart Citation
“…The study revealed that serious accidents frequently occurred at sites of less than 0.008 billion USD in South Korea. Collectively, these studies, including contributions by Daba et al [10] and Berhe et al [11], consistently show that workers in smaller construction sites are at a higher risk compared to those in larger settings.…”
Section: Accident Characteristics In Small-scale Construction Sitesmentioning
confidence: 77%
“…Most studies on improving safety and health at small-scale construction sites have recently focused on identifying the causes of accidents, their occurrences, and the populations of high-risk groups [7][8][9][10][11]. While these studies have significantly contributed to easily understanding the primary causes of accidents, they have overlooked the complex interactions between the complex causes and outcomes of accidents.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Metal sectors have a greater rate of occupational injuries and majority of employees did not adhere to occupational safety and health standards such as proper use of personal protective equipment. [16][17][18] The prevalence of PPE use was observed to be 76.2% among small-scale metal workers, with the linked characteristics of educational status, job experience, OHS training, and regulatory availability. 19 Studies on the incidence of occupational hazards and injuries in small-scale companies conducted in numerous countries, including Ethiopia, have found a high prevalence of injuries and low compliance with OHS measures.…”
Section: Introductionmentioning
confidence: 99%
“…That is why education and awareness creation are among the 16 packages encompassed in the Ethiopian health extension packages [24]. In spite of all, previous findings concerning the influence of education on PPE utilization remain inconsistent and contradicting [25][26][27], which underscores the need for further investigation.…”
Section: Introductionmentioning
confidence: 99%